Effects of Human Observer Presence on Pain Assessment Using Facial Expressions in Rabbits - Pinho, Renata H.; Justo, André A; Cima, Daniela S. [UNESP]; Fonseca, Mariana W. [UNESP]; Minto, Bruno W. [UNESP]; Rocha, Fabiana D L [UNESP]; Leach, Matthew C.; Luna, Stelio P L [UNESP] (American Association for Laboratory Animal Science, 2023)
The goal of this study was to evaluate the effect of a human observer on Rabbit Grimace Scale (RbtGS) scores. The study scored video footage taken of 28 rabbits before and after orthopedic surgery, as follows: 24 h before surgery ( baseline), 1 h after surgery ( pain), 3 h after analgesia administration ( analgesia), and 24 h after surgery ( 24h) in the presence and absence of an observer. Videos were assessed twice in random order by 3 evaluators who were blind to the collection time and the presence or absence of an observer. Responses to pain and analgesia were evaluated by comparing the 4 time points using the Friedman test, followed by the Dunn test. The influence of the presence or absence of the observer at each time point was evaluated using the Wilcoxon test. Intra- and interrater reliabilities were estimated using the intraclass correlation coefficient. The scale was responsive to pain, as the scores increased after surgery and had decreased by 24 h after surgery. The presence of the observer reduced significantly the RbtGS scores (median and range) at pain (present, 0.75, 0 to 1.75; absent, 1, 0 to 2) and increased the scores at baseline (present, 0.2, 0 to 2; absent, 0, 0 to 2) and 24h after surgery (present, 0.33, 0 to 1.75; absent, 0.2, 0 to 1.5). The intrarater reliability was good (0.69) to very good (0.82) and interrater reliability was moderate (0.49) to good (0.67). Thus, the RbtGS appeared to detect pain when scored from video footage of rabbits before and after orthopedic surgery. In the presence of the observer, the pain scores were underestimated at the time considered to be associated with the greatest pain and overestimated at the times of little or no pain.